VIRILISATION VS NON VIRILISATION: MULTIFACES OF CHILDHOOD ADRENOCORTICAL CARCINOMA (ACC) - M, Sulochana; Idris, AN; The, KH; Zahari, Z; Said, NM; Awang, A; Siah, HH; Talib, A; PG, Lim (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Adrenocortical carcinoma (ACC) is a rare tumour in children. Unlike adults where ACC are non-functional (40%), the majority of tumours in children (94%) are functional. Their presentation varies from virilisation to Cushing syndrome. Early recognition is imperative in their management. We describe 2 children with ACC with different clinical presentations. Case 1: A 2-year-old girl presented with signs of progressive virilisation and abdominal distension for 5 months. Serial growth parameters showed rapid weight gain (crossed from the 3rd to 25th centile) although her height remained at 3rd percentile. She was normotensive. There were deepening of voice, hirsutism, clitoromegaly and pubic hair. There was an irregular hard mass at the left hypochondrium. Blood test showed hyperandrogenism and hypercortisolism. CT scan showed a left adrenal mass with bilateral lung metastases. She underwent resection of the adrenal mass followed by bilateral lung nodulectomies. Histopathological examination confirmed ACC with lung metastases. She had completed concurrent mitotane and chemotherapy. Case 2: A 6-year-old boy presented with hypertensive encephalopathy preceded by rapid weight gain. There were hirsutism and acanthosis nigricans. Ultrasound imaging showed a left adrenal mass, confirmed by CT scan. There was no metastatic disease. Blood test showed hypercortisolism. Complete tumour resection was achieved. Histopathological examination confirmed ACC. CONCLUSION ACC is potentially fatal. Since ACC in children is functional, it is hoped that increased familiarity with its presentation will result in earlier diagnosis, intervention and improvement in their overall survival.